Uterine Sarcoidosis: A Rare Extrapulmonary Site of Sarcoidosis - Creticus P. Marak; Narendrakumar Alappan; Amit Chopra; Olena Dorokhova; Sumita Sinha; Achuta K. Guddati (Case Reports in Rheumatology)
Sarcoidosis is a multisystem disease which is most commonly manifested in the pulmonary system. However, extrapulmonary manifestations have also been frequently reported. Isolated occurrence of sarcoidosis in the genital system is rare and poses a diagnostic and therapeutic dilemma. Uterine sarcoidosis can present with cervical erosions, endometrial polypoid lesions, and recurrent serometra. In majority of cases, it is diagnosed by endometrial curettage, but it has also been detected by examination of hysterectomy, polypectomy, and autopsy specimens. Nonnecrotizing granulomas are the characteristic pathologic finding of sarcoidosis. However, many infectious and noninfectious etiologies including certain neoplasms can produce similar granulomatous reactions in the female genital tract. These conditions affect the female genital tract more commonly than sarcoidosis, and therefore it is important to rule out these conditions first before making a diagnosis of sarcoidosis. Treatment of sarcoidosis is different from treating these other conditions and the most commonly used systemic or local corticosteroids can be hazardous if the underlying cause is infection. In this case report, the clinical presentation, histopathology, clinical course, and treatment of a patient with isolated uterine sarcoidosis are described, and a brief literature review of sarcoidosis of the female genital tract is provided.